MAP Kinase Pathways in the Yeast Saccharomyces cerevisiae - Gustin, Michael C. (American Society for Microbiology, 1998)
A cascade of three protein kinases known as a mitogen-activated protein kinase (MAPK) cascade is commonly found as part of the signaling pathways in eukaryotic cells. Almost two decades of genetic and biochemical experimentation plus the recently completed DNA sequence of the Saccharomyces cerevisiae genome have revealed just five functionally distinct MAPK cascades in this yeast. Sexual conjugation, cell growth, and adaptation to stress, for example, all require MAPK-mediated cellular responses. A primary function of these cascades appears to be the regulation of gene expression in response to extracellular signals or as part of specific developmental processes. In addition, the MAPK cascades often appear to regulate the cell cycle and vice versa. Despite the success of the gene hunter era in revealing these pathways, there are still many significant gaps in our knowledge of the molecular mechanisms for activation of these cascades and how the cascades regulate cell function. For example, comparison of different yeast signaling pathways reveals a surprising variety of different types of upstream signaling proteins that function to activate a MAPK cascade, yet how the upstream proteins actually activate the cascade remains unclear. We also know that the yeast MAPK pathways regulate each other and interact with other signaling pathways to produce a coordinated pattern of gene expression, but the molecular mechanisms of this cross talk are poorly understood. This review is therefore an attempt to present the current knowledge of MAPK pathways in yeast and some directions for future research in this area.